Information security superheroes / Nurul Amirah Md Suhaimi and Nurul Aishah Samin - Md Suhaimi, Nurul Amirah; Samin, Nurul Aishah (Faculty of Information Management, 2015)
This paper discussed about the information security careers that describe about the role, responsibility and importance of each career in the organization. The criteria for those who works in this field also being stated. This paper also to investigate the different career in Information Security which has a different roles and responsibility that were related to information system and network system. Other than that, this paper discussed about the agency that involves information security in Malaysia which is Malaysian Communication and Multimedia Commission (MCMC).